Brexit and its Impact on the Co-Operation Along with the 21st Century Maritime Silk Road—Assessment from Port Governance - Khan, Mehran Idris; Lokhande, Sumedh; Chang, Yen-Chiang (Frontiers in Marine Science, 2022)
Since the Brexit happened in January 2020, it is likely to impact the United Kingdom (UK) and the whole of Europe in different ways. The UK and other European countries will revise their preferences concerning fisheries, ports access and governance, and bilateral diplomatic relationships with the countries alongside the 21st Century Maritime Silk Road (MSR). However, this is not an end to uncertainties, but the beginning to show the double-edged effects of Brexit. This paper focuses on the opportunities and challenges for Sino-UK as well as European Union (EU) relations arising from Brexit. The present study considers Brexit’s impact on the MSR countries, especially China, Pakistan, and India. It adopts qualitative means to examine what Brexit means for the Sino-UK/EU relationship, politically, economically, and culturally. It also provides an analysis of the impact of Brexit on maritime security, marine resources usage, the safety of navigation, port governance and cooperation, and so on. To this end, it concludes with the potential impacts of Brexit on Sino-UK/EU trade relations, and suggests the appropriate strategies that can be put in place to capitalise on opportunities to reap benefits while mitigating the challenges.